Pengaruh Corporate Image dan Good Corporate Governance Terhadap Loyalitas Melalui Kepuasan Nasabah Bank Syariah Indonesia - prasetya, giverra putri (Universitas Muhammadiyah Sumatera Utara, 2025)
Although the islamic banking sector in Indonesia is still growing, retaining customers is one of the biggest challenges. This research aims to determine the extent of the influence of corporate image and good corporate governance on customer loyalty at Bank Syariah Indonesia with customer satisfaction as a mediating variable. This research employs a quantitive approach using primary data through the spread of questionnaire online by customers in Pati, Kudus, and Jepara which was analyze SEM-PLS use SmartPLS 3.0 version. The result show that corporate image does not have a direct or an indirect effect on customer loyalty with customer satisfaction as an intervening variable. Nevertheless, good corporate governance directly affects customer loyalty and indirectly through customer satisfaction as an intervening variable. Customer satisfaction has an significant effect on customer loyalty. The result suggest that Bank Syariah Indonesia must increase the relevance of the corporate image program also strengthen the good corporate governance management. Customer satisfaction is the key to maintaining loyalty.